2017
DOI: 10.1002/2017ja023966
|View full text |Cite
|
Sign up to set email alerts
|

Effects of solar proton events on dayglow observed by the TIMED/SABER satellite

Abstract: The effect of solar proton events on the daytime O2 and OH airglows and ozone and atomic oxygen concentrations in the mesosphere is studied using data from the Sounding of the Atmosphere using Broadband Emission Radiometry (SABER). Five events occurred in September 2005, December 2006, March 2012, May 2013, and June 2015 that satisfy two criteria: the maximum proton fluxes are larger than 1000 pfu, and daytime data in the high latitude region are available from SABER. The event in December 2006 is studied in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…Many studies have reported that geomagnetic activity can significantly affect global mesospheric composition through energetic particle precipitation into the middle atmosphere. This leads to a large increase in odd nitrogen and odd hydrogen, and a strong depletion of ozone in the global mesosphere (e.g., Andersson, Verronen, Rodger, Clilverd, & Wang, ; Andersson, Verronen, Rodger, Clilverd, & Seppälä, ; Daae et al, ; Gao et al, ; Jackman et al, ; Solomon et al, , and references therein). A few studies have found evidence for mesospheric temperature enhancements in polar and higher midlatitudes regions during geomagnetic storms (e.g., Hocke, ; von Savigny et al, ; Yuan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that geomagnetic activity can significantly affect global mesospheric composition through energetic particle precipitation into the middle atmosphere. This leads to a large increase in odd nitrogen and odd hydrogen, and a strong depletion of ozone in the global mesosphere (e.g., Andersson, Verronen, Rodger, Clilverd, & Wang, ; Andersson, Verronen, Rodger, Clilverd, & Seppälä, ; Daae et al, ; Gao et al, ; Jackman et al, ; Solomon et al, , and references therein). A few studies have found evidence for mesospheric temperature enhancements in polar and higher midlatitudes regions during geomagnetic storms (e.g., Hocke, ; von Savigny et al, ; Yuan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we use proton flux measurements from the Geostationary Operational Environmental Satellites (GOES), Rodriguez et al (2010) and ozone data from WACCM-D. These satellites for ozone data were chosen as they have previously been used to investigate SPE impact on middle atmospheric ozone, see for example, for MIPAS (Funke et al, 2011;López-Puertas et al, 2005), OSIRIS (Degenstein et al, 2005), MLS (Andersson et al, 2016;Jia et al, 2020;Verronen et al, 2006) and SABER (Gao et al, 2017;Päivärinta et al, 2013). The GOES satellites carry an energetic particle sensor and have provided continuous solar proton flux measurements since 1974 (Rodriguez et al, 2010).…”
Section: Data and Model Descriptionmentioning
confidence: 99%